The gasoline fuel quality impact on fuel consumption, air-fuel ratio (AFR), lambda (λ) and exhaust emissions of gasoline-fueled vehicles. Issue 1 (1st January 2019) - Flamarz Al-Arkawazi, Shamil Ahmed
Abstract: Improving the gasoline fuel combustion, reducing gasoline fuel consumption and reducing vehicles exhaust emissions pollution associated with gasoline combustion become growing interest locally and global-wide. To satisfy the exhaust gas emissions rules and regulations and reducing fuel consumption, it is very significant and critical to determine and understand the gasoline fuel quality impact on fuel consumption, air-fuel ratio (AFR), lambda (λ) and exhaust emissions of gasoline-fueled vehicles. Therefore, studying the impact of gasoline fuel quality on fuel consumption, the air-fuel ratio (AFR), lambda (λ) and exhaust emissions of gasoline-fueled vehicles is very important and necessary. A sensitive and detailed analysis conducted to analyze and determine the impact of gasoline fuel quality on fuel consumption, air-fuel ratio (AFR), lambda (λ) and exhaust emissions of gasoline-fueled vehicles. The study results indicated a direct impact of gasoline fuel quality on fuel consumption, the air-fuel ratio (AFR), lambda (λ) and some vehicle exhaust gases emission including carbon dioxide (CO2), oxygen (O2) and nitrogen oxides (NOx). Also, the results indicated the indirect impact of gasoline fuel quality on hydrocarbons (CxHy) vehicle exhaust emission. The results of this study can help in reducing fuel consumption, improving the quality of fuel combustion and reducing vehicle exhaust emissions.